Gender Differences in the Relationships Between Coach Transformational Leadership and Player Satisfaction and Commitment: A Meta-Analytic Review - Kim, Hyun-Duck; Cruz, Angelita Bautista (Frontiers in Psychology, 2022)
This study meta-analyzed the relationships between coach transformational leadership and player satisfaction and commitment. We also examined the potential moderating effect of player gender on these relationships. In total, 182 effect sizes were obtained from 26 studies comprised of 6,715 participants. The analyses revealed that the overall direct effect of transformational leadership was moderate on both athletic satisfaction and exercise commitment. The effect of charismatic construct of transformational leadership was moderate on athletic satisfaction as well as exercise commitment. Finally, player gender was found to moderate the effects of the relationship between transformational leadership and athletic satisfaction and exercise commitment of players. Specifically, female players' satisfaction and commitment were more positively affected by transformational leadership compared with their male counterparts. Our findings suggests that effective leadership in sports is dependent on the interaction among leadership behaviors of the coach, personal characteristics of the players, and situational factors and highlights the importance of transformational leadership as an important requirement for creating a more positive and sustainable sports environment.